2020
DOI: 10.1111/jcmm.15079
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin prevents the progression of osteoarthritis by targeting PI3K/Akt/NF‐κB axis: In vitro and in vivo studies

Abstract: Osteoarthritis (OA), which is principally featured by progressive joint metabolic imbalance and subsequent degeneration of articular cartilage, is a common chronic joint disease. Arctigenin (ATG), a dietary phyto-oestrogen, has been described to have potent anti-inflammatory effects. Nevertheless, its protective effects on OA have not been clearly established. The target of our following study is to evaluate the protective effects of ATG on IL-1β-induced human OA chondrocytes and mouse OA model. Our results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
(66 reference statements)
3
13
0
Order By: Relevance
“…Arctigenin protected against LPS-induced lung inflammatory and oxidative damage [ 153 ], and, in IL-1β–induced human osteoarthritis (OA) chondrocytes and mouse OA model, the lignan effectively decreased the level of pro-inflammatory mediators attenuating the progression of OA [ 189 ]. Arctigenin inhibited allergic inflammation type I as heterologous passive cutaneous anaphylaxis, type II as reversed cutaneous anaphylaxis, type III as the sheep red blood cell-induced Arthus reaction and contact dermatitis (type IV hypersensitive inflammation) in vivo as well as suppressed pro-inflammatory enzymes, such as COX, LOX, phospholipase A2 (PLA 2 ), and phosphodiesterase (PDE), in vitro [ 186 ].…”
Section: Lignans With Antioxidant and Anti-inflammatory Actionmentioning
confidence: 99%
“…Arctigenin protected against LPS-induced lung inflammatory and oxidative damage [ 153 ], and, in IL-1β–induced human osteoarthritis (OA) chondrocytes and mouse OA model, the lignan effectively decreased the level of pro-inflammatory mediators attenuating the progression of OA [ 189 ]. Arctigenin inhibited allergic inflammation type I as heterologous passive cutaneous anaphylaxis, type II as reversed cutaneous anaphylaxis, type III as the sheep red blood cell-induced Arthus reaction and contact dermatitis (type IV hypersensitive inflammation) in vivo as well as suppressed pro-inflammatory enzymes, such as COX, LOX, phospholipase A2 (PLA 2 ), and phosphodiesterase (PDE), in vitro [ 186 ].…”
Section: Lignans With Antioxidant and Anti-inflammatory Actionmentioning
confidence: 99%
“…The IC 50 value for MKK1 in vitro was 1 nM [ 186 ]. In another study, it was demonstrated that arctigenin interacts with PI3K, and IL-1β-stimulated PI3K and Akt phosphorylation could be inhibited by pre-treatment with arctigenin [ 187 ].…”
Section: Natural Compounds As Kinase Inhibitorsmentioning
confidence: 99%
“…Osteoarthritis (OA) is a common chronic joint disease [8] and is characterized by the destruction of articular cartilage, sclerosis of subchondral bone, and inflammation of the synovium [11]. Aging is a primary risk factor for OA [12].…”
Section: Discussionmentioning
confidence: 99%
“…AMPK signaling plays a regulatory role in the chondrocyte apoptosis and cartilage degeneration of OA rat models [7]. In addition, lots of studies have suggested that the occurrence and development of osteoarthritis are related to the excessive activation of NF‐κB [8]. NF‐κB signaling pathway is implicated in the proliferation and apoptosis of OA chondrocytes [9] and has been suggested as the therapeutic target for OA [10].…”
mentioning
confidence: 99%